Long-Term Outcomes of Real-World Korean Patients with Atrial-Fibrillation-Related Stroke and Severely Decreased Ejection Fraction - Jung, Jin-Man (J Clin Neurol, 2019)
BACKGROUND AND PURPOSE: The clinical implications of echocardiography findings for long-term outcomes in atrial fibrillation (AF)-related stroke patients are unknown. METHODS: This was a substudy of the Korean ATrial fibrillaTion EvaluatioN regisTry in Ischemic strOke patieNts (K-ATTENTION), which is a multicenter-based cohort comprising prospective stroke registries from 11 tertiary centers. Stroke survivors who underwent two-dimensional transthoracic echocardiography during hospitalization were enrolled. Echocardiography markers included the left-ventricle (LV) ejection fraction (LVEF), the left atrium diameter, and the ratio of the peak transmitral filling velocity to the mean mitral annular velocity during early diastole (E/e′ ratio). LVEF was categorized into normal (≥55%), mildly decreased (>40% and <55%), and severely decreased (≤40%). The E/e′ ratio associated with the LV filling pressure was categorized into normal (<8), borderline (≥8 and <15), and elevated (≥15). Kaplan-Meier and Cox regression analyses were performed for recurrent stroke, major adverse cardiac events, and all-cause death. RESULTS: This study finally included 1,947 patients. Over a median follow-up of 1.65 years (interquartile range, 0.42–2.87 years), the rates of recurrent stroke, major adverse cardiac events, and all-cause death were 35.1, 10.8, and 69.6 cases per 1,000 person-years, respectively. Multivariable analyses demonstrated that severely decreased LVEF was associated with a higher risks of major adverse cardiac events [hazard ratio (HR), 3.91; 95% confidence interval (CI), 1.58–9.69] and all-cause death (HR, 1.95; 95% CI, 1.23–3.10). The multivariable fractional polynomial plot indicated that recurrent stroke might be associated with a lower LVEF. CONCLUSIONS: Severe LV systolic dysfunction could be a determinant of long-term outcomes in AF-related stroke.